The EVALUATION OF STUDENT SATISFACTION IN THE MASTER'S PROGRAM IN SPORTS TRAINING EDUCATION REGARDING THESIS PROPOSAL LECTURE MATERIALS: EVALUATION OF STUDENT SATISFACTION IN THE MASTER'S PROGRAM IN SPORTS TRAINING EDUCATION REGARDING THESIS PROPOSAL LECTURE MATERIALS - Endang Rini Sukamti; Muhammad Wahyu Arga; Okky Indera Pamungkas; Sri Ayu Wahyuti; Kukuh Hardopo Putro (Universitas Negeri Yogyakarta, 2025)
Writing scientific papers in the form of thesis proposals and theses is one of the mandatory requirements for students completing a master's degree program. However, to date, this remains a problem for many students, both in terms of the work involved and the time required to complete it. Non-academic and academic difficulties are the triggers. Non-academic difficulties often encountered by students are dominated by personal readiness, including the large number of students who are lazy to start writing. Furthermore, academic constraints include writing difficulties. Based on the results of several previous studies, this became a reference for researchers to observe the conditions of students in the Master's Program in Sports Coaching Education. The aspect that will be observed from an academic perspective is related to student satisfaction with thesis writing courses in the Master's Program in Sports Coaching Education. This study uses a non-experimental quantitative method that aims to describe students' perceptions of the final assignment writing material provided. The population in this study consisted of 90 AKIF students. The sampling technique used was purposive sampling, resulting in a sample size of 53 people. The research instrument used a closed-ended questionnaire so that the results could be obtained in a comprehensive and accurate manner. Based on the descriptive analysis results, it can be concluded that the overall level of student satisfaction is very high. This is indicated by the dominance of “very satisfied” answers (average >70%) in almost all evaluation items, reflecting that the thesis proposal lectures have been carried out well and in accordance with student needs.